Pemanfatan Lahan Untuk Budidaya Hortikultura Melalui Pemberdayaan KWT Kecubung Batu Di Desa Blawong 1 - Ismiasih, Ismiasih; Dinarti, Siwi Istiana; Afroda, Helmi (Madani : Indonesian Journal of Civil Society, 2024)
Empty land is often found in the community environment without being used for productive activities, such as in Blawong Village 1. This community service aims to foster awareness and independence of the Women Farmers Group (KWT) in land utilization through horticultural cultivation activities. The method of community service activities is carried out by empowering KWT "Kecubung Batu" through the PRA (Participatory Rural Appraisal) method, namely by involving each member in the active role of the activity. The form of community service activities is in the form of counseling and training in horticultural cultivation by making demonstration plots (demonstration plots) on empty land. Based on data that has been collected through field observations (observations) and interviews by providing questionnaires, the results obtained that almost 100% of community service activities have succeeded in increasing insight and skills for KWT Kecubung Batu in horticultural cultivation. In addition, the increase in insight and skills of KWT "Kecubung Batu" in utilizing the land for horticultural cultivation has also almost reached 100%. This is indicated by the results of community service activities, KWT â€œKecubung Batuâ€ has a productive garden as a means of empowering its members with horticultural cultivation.